Importance of seller’s ethical behaviour and its Impact on sales performance at the sole proprietorship level businesses in Jalalabad market of Afghanistan - Obaid, Nasratullah; Tariq, Ahmad; Shinwari, Obaidullah; Shorish, Ihsanullah; Sha, Syed Sajad Ali (Eximia, 2023)
It’s crucial for businesses to have trusted customers. To have trusted customers, sellers need quality ethics. Customer loyalty, customer decision to buy, satisfaction, competitive advantage, perceptions, sales force output, and buyer-seller relations can help in creating a long-term customer base, which has an important role in businesses' sales performance. The main aim of the research was to determine the impact of a seller’s ethics on their sales performance in Jalalabad, Afghanistan. Primary data for the study were obtained from lecturers, School Teachers, Office workers, Traffics and employers and some others. In order to select a sample for the study, we used a non-probability technique. In non-probability, we chose convenience and quota sampling technique. 400 questionnaires were given to the respondents. For analysing primary data, we used SPSS software and the OLS method. Besides, we checked different relevant assumptions of the OLS method. Dimensions for seller man's ethics were acceptable ethics, greeting, mutual respect, happiness, quality service, honesty, and planning to continue purchasing and truthfulness. Whereas traffic, product turnover, good market share, product shortage, sales volume, and need fulfillment were dimensions for sales performance. We used structured questions to gain the answers for each dimension, and the questions were used collectively to give the meaning of each variable. The result of the study finally indicated that seller ethics are important and have a strong positive impact on sole proprietorship sales performance working in the Jalalabad market in Afghanistan.